How to Enhance Speaking Skills in an EFL Class Through Flipped Learning (2024)
ABSTRACT: This study was an action research project designed to understand how flipped learning can enhance language speaking skills in a group of ninth graders. The participants, aged between 14 and 16 years old, comprised a total of 41 students. Data was collected through class observations, interviews, and questionnaires. A review of the collected data revealed that flipped learning was generally effective in enhancing students' accuracy and participation through the use of videos, grammar exercises, online pronunciation platforms, and after-reading exercises. While fluency was partially improved, additional strategies are recommended to achieve better outcomes in this area.